Repositioning the Racial Gaze: Aboriginal Perspectives on Race, Race Relations and Governance - Daphne Habibis; Penny Taylor; Maggie Walter; Catriona Elder (Social Inclusion, 2016)
In Australia, public debate about recognition of the nation’s First Australians through constitutional change has highlighted the complexity and sensitivities surrounding Indigenous/state relations at even the most basic level of legal rights. But the unevenness of race relations has meant Aboriginal perspectives on race relations are not well known. This is an obstacle for reconciliation which, by definition, must be a reciprocal process. It is especially problematic in regions with substantial Aboriginal populations, where Indigenous visibility make race relations a matter of everyday experience and discussion. There has been considerable research on how settler Australians view Aboriginal people but little is known about how Aboriginal people view settler Australians or mainstream institutions. This paper presents the findings from an Australian Research Council project undertaken in partnership with Larrakia Nation Aboriginal Corporation. Drawing on in-depth interviews with a cross-section of Darwin’s Aboriginal residents and visitors, it aims to reverse the racial gaze by investigating how respondents view settler Australian politics, values, priorities and lifestyles. Through interviews with Aboriginal people this research provides a basis for settler Australians to discover how they are viewed from an Aboriginal perspective. It repositions the normativity of settler Australian culture, a prerequisite for a truly multicultural society. Our analysis argues the narratives of the participants produce a story of Aboriginal rejection of the White Australian neo-liberal deal of individual advancement through economic pathways of employment and hyper-consumption. The findings support Honneth’s arguments about the importance of intersubjective recognition by pointing to the way misrecognition creates and reinforces social exclusion.